2-[2-(1H-indol-3-yl)ethyliminiomethyl]-4-nitrophenolate - Ali, Hapipah Mohd; Mustafa, M.I.M.; Rizal, Mohd Razali; Ng, Seik Weng (International Union of Crystallography, 2008)
The title Schiff base, C17H15N3O3, exists in the zwitterionic form with the phenol H atom transferred to the imine group. Adjacent zwitterions are linked into a linear chain running along the a axis by an indole-hydroxy N-H center dot center dot center dot O hydrogen bond [3.100 (2) angstrom].